Echo’s revenge. Ovid’s Metamorphoses and Spike Jonze’s her - Marco Formisano (Eugesta, 2021)
How productive can a comparison be between an ancient Latin text and a modern film? What are the methodological implications and how might this comparison fundamentally change the perception and interpretation of both text and film? In this article Spike Jonze’s film her (2013) and the episode of Echo and Narcissus in Ovid’s Metamorphoses (book 3) are discussed together, not because it is possible to establish a direct influence of the Latin poem on the work of the American director, but because of a shared central theme, that of voice, in particular a female voice. While reception studies more traditionally seek to reconstruct and demonstrate influences of one work on another, I argue that Donna Haraway’s “diffractive reading” and Hartmut Böhme’s “allelopoiesis” can generate complex and nuanced reading since they productively illuminate the interdependency of the two comparanda. In other words, not only can we better appreciate the role of the female voice in her after having read Ovid’s Echo, but by considering its protagonist Samantha we can appreciate aspects of Echo never considered before. The comparison is rewarding from another perspective as well: it illuminates textuality in the movie and filmic aspects of the text.